1998
DOI: 10.1021/ic971466u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Structure, and Properties of a Neutral Schiff Base Phenolic Complex of Magnesium

Abstract: A neutral bis(salicylaldimine) Mg complex has been synthesized, representing the first stable Schiff base phenoxo complex of Mg involving the participation of two phenolic oxygens and four nitrogens. While the crystal structure of the Mg complex was determined to be highly similar to those of known cationic Ga(III) and Fe(III) complexes, in contrast, the Mg complex did not show significant differential cytotoxicity between drug-sensitive and multidrug-resistant cancer cells expressing MDR1 P-glycoprotein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(44 reference statements)
1
8
1
Order By: Relevance
“…1 H NMR data suggested that 85% of the parent compound remained after a 72 h incubation in solution containing an equimolar mixture of Mg 2+ and HPO 4 2- /H 2 PO 4 - ions at pH 7.4. Lowering the pH or deleting Mg 2+ ions increased the rate of hydrolysis . Cytotoxicity studies (Figure ) in non-Pgp- and Pgp-expressing tumor cell lines demonstrated that the cytotoxicity profiles were not modified by expression of MDR1 Pgp.…”
Section: Neutral Metal Complexesmentioning
confidence: 96%
See 3 more Smart Citations
“…1 H NMR data suggested that 85% of the parent compound remained after a 72 h incubation in solution containing an equimolar mixture of Mg 2+ and HPO 4 2- /H 2 PO 4 - ions at pH 7.4. Lowering the pH or deleting Mg 2+ ions increased the rate of hydrolysis . Cytotoxicity studies (Figure ) in non-Pgp- and Pgp-expressing tumor cell lines demonstrated that the cytotoxicity profiles were not modified by expression of MDR1 Pgp.…”
Section: Neutral Metal Complexesmentioning
confidence: 96%
“…Lowering the pH or deleting Mg 2+ ions increased the rate of hydrolysis. 94 Cytotoxicity studies (Figure 2) in non-Pgp-and Pgp-expressing tumor cell lines demonstrated that the cytotoxicity profiles were not modified by expression of MDR1 Pgp. These data suggested that compound 25 was not interacting with Pgp.…”
Section: Neutral Metal Complexesmentioning
confidence: 97%
See 2 more Smart Citations
“…Although modest (<0.5 ppm) chemical shift changes are observed due to the presence of radical-mediated decomposition product, 17 To evaluate the structural consequences giving rise to such facile thermal reactivity, molecular mechanics calculations at the MMX force field level 18 have been performed for enediyne ligand 3, as well as a series of four-to six-coordinate Mg 2+ structures. Since Mg 2+ is electrophilic and frequently forms five-coordinate [19][20][21][22][23] or six-coordinate 21,[24][25][26][27][28][29][30][31] structures in the presence of anionic ligands and coordinating solvents, the geometric starting point for the latter calculations was the five-or six-coordinate MgN 4 O x (x ) 1, 2) construct where OHwas used to approximate solvent (MeOH) or counterion (Cl -) coordination in solution. Within these coordination environments, approximately 60 structures were iteratively minimized until a subset of five of the lowest-energy structures for each class were identified.…”
mentioning
confidence: 99%